1998
DOI: 10.2307/3284537
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Characterization of Experimental Cutaneous Leishmaniasis in Mice Infected with Leishmania braziliensis in the Presence or Absence of Sand Fly Vector Salivary Gland Lysate

Abstract: Leishmania braziliensis is the causative agent of human cutaneous leishmaniasis in parts of the New World. In the murine model of infection, L. braziliensis does not produce severe or lasting cutaneous lesions in either BALB/c or C3H mice. However, when the parasites are injected into BALB/c mice with salivary gland lysate of the sand fly vector for the parasite, infection is significantly enhanced, as measured by lesion size, parasite burden, and the outcome of infection. Histologic examination of these cutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 15 publications
3
24
0
5
Order By: Relevance
“…These effects are implicated in the ability of saliva to exacerbate Leishmania infection [10, 11,[15][16][17][18][19]. In the present study we demonstrated that Lutzomyia saliva also inhibits the effector phase of a Th1 immune response.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These effects are implicated in the ability of saliva to exacerbate Leishmania infection [10, 11,[15][16][17][18][19]. In the present study we demonstrated that Lutzomyia saliva also inhibits the effector phase of a Th1 immune response.…”
Section: Discussionsupporting
confidence: 59%
“…In leishmaniasis, there is evidence that the saliva of the vectors Lutzomyia and Phlebotomus contains substances with immunosuppressor, vasodilatator, anti-platelet and anticlotting activities [8][9][10][11][12][13]. In addition to increasing the hemorrhagic pool where sand flies feed [8,14], salivary components also induce host immunosuppression, which is fundamental for the establishment of Leishmania infection [10,[15][16][17][18][19] production and antigen presentation by infected macrophages [20][21][22]. Furthermore, they inhibit Th1 induction, enhancing the Th2-type response with an increase of IL-4 and IL-10 in the infection [23][24][25].…”
mentioning
confidence: 99%
“…In this study, dermal lesions were observed following the inoculation of 10 5 stationary-phase parasites whereas previous studies using this same parasite strain showed that the inoculation of 10 7 parasites into the footpads of BALB/c mice leads to, comparatively, mild increases in footpad thickness (22). In the footpad model, BALB/c mice infected with L. braziliensis develop a local inflammation consisting of epithelioid macrophages and polymorphonuclear cells (19,22). These same cell populations were recruited to the ear dermis.…”
Section: Discussionmentioning
confidence: 42%
“…To define the mechanism underlying this phenomenon, the effects of SGH on various immune functions were examined. SGH, whose components may have unique, synergistic, or antagonistic activities, have been reported to affect iNOS activity, the Th1-Th2 balance, and the persistence of neutrophils and eosinophils at sites of Leishmania infection (10,20,28,29,43). In addition, injecting sand fly saliva into normal but not scid mice induced IL-4 production at the dermis and in draining lymph nodes (5,25).…”
mentioning
confidence: 99%